Embodied experience and identification: Exploring the role of curating a Rwandan Cultural Group’s Song and Dance in shaping Impunzi sense of identity - Ilibagiza Mutabazi, Gratia Aimee (Stellenbosch : Stellenbosch University, 2025)
Thesis (MA)--Stellenbosch University, 2025.